2008
DOI: 10.1136/jech.2007.066191
|View full text |Cite
|
Sign up to set email alerts
|

Social and economic correlates of depressive symptoms and perceived stress in South African adults

Abstract: Depressive symptoms and perceived stress are public health concerns in this sample, with more symptoms among those with fewer resources. The prevention of mental illness is critical, especially in vulnerable populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
138
2
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(164 citation statements)
references
References 47 publications
20
138
2
4
Order By: Relevance
“…The results of the presented study concerning Eastern Poland generally correspond to the results of studies from other countries (Norway, Hungary, South Africa, USA and Netherlands), and indicate a relationship between the socioeconomic position, and self-assessment of health status [35,36,37,38,39,7]. Research conducted by K. M. Olsen and S. A. Dahl [13] concerning the differences in the health of residents of 21 European countries showed that the health status of the population in the analysed countries depended on a variety of political, socio-economic and behavioural characteristics.…”
Section: Discussionmentioning
confidence: 51%
“…The results of the presented study concerning Eastern Poland generally correspond to the results of studies from other countries (Norway, Hungary, South Africa, USA and Netherlands), and indicate a relationship between the socioeconomic position, and self-assessment of health status [35,36,37,38,39,7]. Research conducted by K. M. Olsen and S. A. Dahl [13] concerning the differences in the health of residents of 21 European countries showed that the health status of the population in the analysed countries depended on a variety of political, socio-economic and behavioural characteristics.…”
Section: Discussionmentioning
confidence: 51%
“…However, depression exists at possibly higher prevalence rates than in western countries 37 according to 16 studies 4,5,7,[9][10][11][38][39][40][41][42][43][44][45][46][47] , and an additional 13 studies cited in 37 , of community and non-HIVspecific clinic populations, with generally higher rates for women than men 37,43 . Finally, depression is reasonably easy to elicit when sought and present 37 .…”
Section: Introductionmentioning
confidence: 99%
“…In the past, these scales were used in many South African studies and in many different contexts (Cilliers & Coetzee, 2003;Fourie, Rothmann & Van de Vijver, 2008;Hamad, Fernald, Karlan & Zinman, 2008;Rothmann, Steyn & Mostert, 2005;Strümpfer & Mlonzi, 2001;Strümpfer, Viviers & Gouws, 1998;Strümpfer & Wissing, 1998;Temane & Wissing, 2006;Westaway, Maritz & Golele, 2003;Wissing & Van Eeden, 2002;Wissing, Wissing, Du Toit & Temane, 2008). Whereas the salutogenic or fortigenic approach and positive psychology were initially viewed as a new academic movement or sub-discipline, they are now increasingly becoming an applied field in community, clinical and work contexts.…”
Section: Introductionmentioning
confidence: 99%